Physical characteristics of mithun of north-east India - HELI, T; SAIKIA, S; BORA, N N (The Indian Journal of Animal Sciences, 2013)
A study was conducted on S6 mithuns of either sex at 1, 12, 24, 36 and above 36 months of age undor the prevailing managemental practices in Lower Subansiri and Papum-pare districts of Arunachal Pradesh. The average values of head conformation, viz. head length, width of fore-head, eye to eye space, muzzle circumferences and ear length of male mithuns were greater than those of female mithuns at different age groups. The hom lenglh was not different (p<0.05) between male and female mithuns. The neck circumference was greater in males Ihan in females, the difference being significant (p<0.05) but the neck length was nonsignificant in both the sexes. The height of the mithun was noted 5 times the length of fore-shank. No Significant difference was evident in any of the body parameters and limbs between male and female mithuns. The tail length was almost similar in bolh the sexes.